PENGARUH FOMO (FEAR OF MISSING OUT) TERHADAP SELF-ESTEEM REMAJA DI SMAN 1 SRESEH SAMPANG - Safitri, Nurlaila; Hasanah, Iswatun; Wahyuningrum, Sri Rizqi (Cognitive: Jurnal Pendidikan dan Pembelajaran, 2025)
With the rapid development of technology, teenagers tend to spend more time on social media. The FOMO phenomenon is very susceptible to teenagers, because they are in the phase of searching for identity. At this stage, teenagers are highly influenced by their social environment and have a high need to be accepted by their group. This condition gives rise to the FOMO (Fear of Missing Out) phenomenon, which is thought to affect self-esteem levels. This study aims to determine the effect of FOMO on self-esteem in teenagers at SMAN 1 Sreseh, Sampang. The method in this study is a comparative causal quantitative approach (Linear Regression). A total of 82 respondents were the objects of this study. Before measuring the effect, an assumption test was conducted that was fully met. The linearity test showed a significance value of 0,280, so the relationship between the variables is linear. The results of the regression test showed a positive and significant influence between FOMO and self-esteem, with a significance value of 0,000 (<0,05). The coefficient of determination (R²) of 0,353 indicates that FOMO contributed 35,3% to students' self-esteem. This study provides a new perspective that FOMO is not always negative, but can be a way for students to maintain their social presence in their social circle.